Da'wah of Islam in the Era of Generation Z: Study of Takhrij and Syarah Hadith - Salsabila, Hasna Rafidah; Qodri, Azizi (Journal of Takhrij Al-Hadith, 2022)
This study aims to discuss hadiths about Islamic da'wah in the Z generation era. This research uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about Islamic da'wah in the Z generation era in the history of Bukhari No. 1365. The results and discussion of this study indicate that the status of this hadith is of authentic quality which is maqbul ma'mul bih as evidence. This study concludes that the hadith narrated by Bukhari No. 1365 is relevant to be used as motivation in spreading Islamic da'wah with various delivery methods, especially in generation Z.